A prospective study of falls in relation to freezing of gait and response fluctuations in Parkinson's disease. (January 2018) - Okuma, Yasuyuki; Silva de Lima, Ana Lígia; Fukae, Jiro; Bloem, Bastiaan R.; Snijders, Anke H.
Abstract: Introduction: Falls are a disabling feature of Parkinson's disease (PD). In this prospective study we investigated: (1) in which motor state patients with PD fallmost often; and (2) whether freezing of gait (FOG) and dyskinesias contribute to falls. Methods: Patients with PD who had fallen at least once in the previous year and had wearing-off were recruited. During six months, patients complete a standardized fall report. We analyzed data regarding fall circumstances and motor state at the time of each first 10 falls. Results: We included 36 patients with PD (34 freezers), with mean ± SD age of 67.5 ± 6.3 years and disease duration of 12.4 ± 4.1 years. 50% had Hoehn & Yahr (HY) 2 at ON-state and 56% had a HY 4 at OFF. All 36 patients fell at least once during the follow-up period (total number of falls: 252; mean ± SD: 19.03 ± 33.9). Falls at ON were 50% of the total falls, followed by Transition (30%) and OFF (20%). Overall, 69% of falls were related to FOG, 28% were unrelated to FOG and 3% were related to dyskinesia. There was a significant relationship between motor state and circumstances (χ2(2) = 31.496, p < 0.001), showing that FOG-related falls happened mostly at OFF-state. Conclusion: This study showed that patients with PD fall mostly at ON. Additionally, FOG is an important contributor to falls in patients with PD. This information may assist clinicians in optimizing medication to prevent further falls. Highlights: We studied the relationship between FOG, falls and motor fluctuation in PD patients. About 50% of falls occurred in the ON-state; half of these ON-state falls were due to FOG. Falls in the OFF-state (20% of falls) and Transition-state (30% of falls) were mainly due to FOG. Contribution of dyskinesia to falls was limited. In any motor state, management of FOG is most important to prevent falls.